Algerian leaders in the Hotel industry in times of transition: an exploratory study on the Mariott and El Djazair groups (مجلة الواحات للبحوث والدراسات, 2026)
This exploratory study examines Marriott and El Djazaïr’s strategies in Algeria in the context of ecological and digital transitions. The methodology combines semi-structured interviews, documentary analysis, and weighted TF-IDF lexical processing structured around five dimensions: international standards and frameworks, heritage and territorial anchoring, institutional and associative partnerships, digital tools and technologies, and socio-economic sustainability. Findings reveal specific forms in their origins and deployment. Marriott operates within recognised global frameworks, integrating connected technologies and management systems to enhance guest experience while reinforcing environmental commitments. El Djazaïr follows a locally rooted approach focused on heritage preservation, prudent resource management, and the promotion of artisanal know-how. The analysis underlines the need to align global standards with territorial specificities to strengthen the economic and environmental viability of the hospitality sector.